TOTAL ULTRASOUND GUIDED PERCUTANEOUS NEPHROLITHOTOMY: A NOVEL TECHNIQUE - Anayat Ullah; Muhammad Kamran Khan; Ata Ur Rahman; Muhammad Naeem; Sarhad Khan; Riaz Ur Rehman (Gomal Journal of Medical Sciences, 2014)
Introduction: Fluoroscopy is commonly used imaging technique during percutaneous nephrolithotomy but is associated with risks of radiation exposure. We evaluated the safety and efficacy of ultrasound guided Percutaneous Nephrolithotomy for treatment of renal stones. Material & Methods: This was a cross-sectional study done at the Department Of Urology and Renal Transplantation, Institute of Kidney Diseases, Hayatabad, Peshawar from July 2010 to June 2012. All procedures were performed in prone position. The location of the target calyx, puncture and dilation of the tract was performed under ultrasound guidance. Stones were broken with Swiss Pneumatic Lithoclast and residual fragments identified by ultrasonography. Results: The lower pole calyx was most commonly punctured, 26 patients (41.9%) followed by middle calyx, 19 patients (30.6%) and upper pole calyx, 17 patients (27.4%). The average procedure time was 71 minutes ± 23.4 minutes (45–110 minutes). The mean hospital stay was 3± 0.9 (2-5) days and nephrostomy tube was kept for 1 (1-3) days. The mean size of stone was 3.0±1.3 (2.5-4.8) cm. Complete clearance was achieved in 54 patients (83%). With dual therapy (PCNL + ESWL/URS), stone clearance was achieved in 58 patients (93.5%). Only one patient required two pints of blood transfusion due to intraoperative bleeding (Hb dropped to 7.4) Other minor complications were mild fever in seven patients, ureteric colic in four patients, and nephrostomy site leakage in six patients. Conclusion: Totally ultrasonography guided PCNL is a good alternative to the fluoroscopic method and has satisfactory outcomes compared with the standard technique of PCNL.